Activated Glucose-6-phosphate Dehydrogenase is Associated with Insulin Resistance by Upregulating Pentose and Pentosidine in Diet-induced Obesity of Rats - Wang, F.; Zhao, Y.; Niu, Y.; Wang, C.; Wang, M.; Li, Y.; Sun, C. (Hormone and Metabolic Research, 2012)
Recent studies have shown that glucose-6-phosphate dehydrogenase (G6PD), the rate-limiting enzyme for the pentose phosphate pathway, was involved in insulin resistance via reduced nicotinamide adenine dinucleotide phosphate, while the roles of pentose were not examined. In the present study, the association of G6PD, pentose, and pentosidine with insulin resistance was investigated in diet-induced obesity of rats. Male Wistar rats were fed a high-fat diet for 6 weeks to generate obesity-prone (OP, n=14) and obesity-resistant (OR, n=14) rats. The levels of G6PD, pentose, and pentosidine, and oxidative stress were analyzed in serum and tissues. The OP rats, compared to the OR and control rats, had a significant increase in body weight (16.2% and 12.8%), serum triglyceride (43.4% and 12.3), and free fatty acids (49.5% and 23.6%), and developed marked insulin resistance. G6PD activities were increased in the pancreas and liver with upregulated pentose levels in serum, pancreas, and liver of OP rats. Pentosidine levels were increased only under the condition of high pentose levels and oxidative stress status in serum and pancreas of OP rats. G6PD activities in pancreas and liver, pentose levels in serum, pancreas, and liver, and pentosidine levels in serum and pancreas were positively correlated with homeostasis model of assessment-insulin resistance. Our results suggest that the upregulation of G6PD causes an increase in the accumulation of pentose and pentosidine, which might be associated with insulin resistance in the condition of obesity.
Keywords: pentose phosphate pathway; oxidative stress; advanced glycation end products